Problematika Pembelajaran Fikih Mawaris pada Mahasiswa Berlatar Belakang Pendidikan SMA di Program Studi Pendidikan Agama Islam Universitas Negeri Padang - Purba, Nur Hafizah; Nurjanah, Nurjanah; Putra, Rido (Darul Yasin Al Sys, 2024)
The problem in learning can obstruct and slow down the learning process, which can become an obstacle to achieving learning objectives. This study aims to identify the problems faced by students with a high school background in the Islamic Religious Education study program in learning Fiqh Mawaris, as well as the efforts made by both students and Islamic Law lecturers to address these issues. The method used is descriptive qualitative with informants including the head of the Islamic Religious Studies Department, two Islamic Law lecturers, and ten students from the Islamic Religious Education program. Data were collected through observation, interviews, and documentation, and then analyzed using data reduction, data presentation, and conclusion drawing techniques. Data validity was tested using source triangulation and technique triangulation. This study found three main problems in the Fiqh Mawaris learning process among students with a high school background: 1) difficulty in understanding the concepts of inheritance classification and distribution, 2) difficulty in analyzing inheritance distribution cases, and 3) challenges faced by students due to their high school educational background. The efforts made by the students to overcome these problems include: 1) writing and memorizing Fiqh Mawaris concepts, 2) seeking additional learning resources, and 3) discussing and studying together. Meanwhile, the lecturers addressed these problems by: 1) delivering material in stages, 2) using discussion and question-and-answer methods, and 3) conducting evaluations and providing feedback to students. The problems in Fiqh Mawaris learning for students with a high school background can be overcome through the active efforts of students seeking additional understanding and through a more structured and interactive teaching approach from the lecturers.